Differentiation of Benign and Malignant Ovarian Tumour by USG and Serum CA-125 (Ibrahim Cardiac Medical Journal, 2023)
Background & objective: Most ovarian tumors are diagnosed at advanced stage, when they have already been spread. There is no reliable diagnostic test or imaging technique available to distinguish benign from malignant cysts. The present study was undertaken to find the diagnostic accuracy of ultrasound and carcinogenic antigen-125 (CA-125) in the differentiation of benign from malignant ovarian tumors.Methods: The study was carried out in the Department of Obstetrics & Gynecology, Rajshahi Medical College Hospital (RMCH), Rajshahi over a period of 2 years from July 2016 to June 2018. Patients attending at RMCH with clinical diagnosis of ovarian tumor (adnexal mass) and sonographically diagnosed as having ovarian mass of >8 cm were included in the study. A total of 75 such cases were consecutively included in the study. The sensitivity, specificity, positive and negative predictive values and overall diagnostic accuracy of ultrasound and CA-125 were judged against histopathological findings. Also, Kappa analysis was done to determine the strength of agreement between the two diagnostic modalities.Result: Age distribution showed that about one-third (32%) of the patients was 50 or > 50 years old with median age of the patients being 40 years (range: 20 – 70 years). Nearly two-thirds (64%) of the patients were multipara and 41.3% were at menopausal stage. Over one-third (34.7%) of the masses were found to be malignant on ultrasonic examination. Over half (52%) of the patients had CA-125 level > 65 U/ml with median CA-125 being 80.7 U/ml. Histopathology reported that 44(58.7%) tumors were benign and the rest 31(41.3%) were malignant. The sensitivity of ultrasound in correctly detecting malignant ovarian tumors was 77.4%, while its specificity in correctly excluding malignancy was 95.4% with overall diagnostic accuracy of the test being 88%. The CA-125 at a cut-off value of 65 although demonstrated a higher sensitivity (83.9%) than USG, its specificity was lower (70.5%) than USG, with overall diagnostic accuracy being 76%. The consistency or strength of agreement between USG & CA-125 in differentiating malignant from benign ovarian tumors was evaluated using kappa-statistics which revealed a moderate agreement between the two diagnostic modalities.Conclusion: The study concluded that ultrasound has optimum sensitivity and high specificity in differentiating malignant ovarian tumors from the benign ones. The CA-125, although exhibits a higher sensitivity than USG, its specificity is lower than USG. A moderate agreement between the two diagnostic modalities was observed. As USG has optimum sensitivity and high specificity with overall diagnostic accuracy being higher than CA-125, USG could be considered superior to CA-125 as a screening test for differentiation of malignant ovarian masses from the benign ones.Ibrahim Card Med J 2021; 11 (2): 33-39